2020
DOI: 10.14569/ijacsa.2020.0110433
|View full text |Cite
|
Sign up to set email alerts
|

Using Concordance to Decode the Ideological Weight of Lexis in Learning Narrative Literature: A Computational Approach

Abstract: In learning narrative literature, students find difficulty in comprehending and approaching the ideological messages beyond the usage of recurrent lexical items in literary narrative texts. This problem comes as a result of the huge number of lexical items literary texts, particularly the narrative, abound in. The use of the computer and of computational linguistics work makes it possible to process and examine large data for a variety of purposes and to investigate questions that could not feasibly be answere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…The majority of these factors were missed with the control group, which, in turn, emphasizes the reason why computer has a great influence on the performance of EFL students. Significantly, the above findings correlate with many previous studies, such as [31][32][33][34][35], [47][48][49].These studies have acknowledged the positive impact of computer in learning English as a foreign language.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of these factors were missed with the control group, which, in turn, emphasizes the reason why computer has a great influence on the performance of EFL students. Significantly, the above findings correlate with many previous studies, such as [31][32][33][34][35], [47][48][49].These studies have acknowledged the positive impact of computer in learning English as a foreign language.…”
Section: Discussionsupporting
confidence: 90%
“…e reasons for this are that some of the traditional teaching methods of "duck and ll" are not up to date with the development of the times and the needs of students, and some of the English classroom teaching strategies and methods are still backward after entering university, and the evaluation system is relatively single, so it is urgent to reform English teaching in university. On the other hand, university students are quick to accept new things, are active in mobile Internet, and rely strongly on smartphones [5,6]. In response to these situations, university teachers are actively exploring ways and means to improve the quality of English teaching, and with the advent of the era of information-based teaching and the widespread use of smartphones, blended teaching based on mobile network environment is one of the more effective ways.…”
Section: Introductionmentioning
confidence: 99%
“…They clarified the extent to which input data can significantly contribute to the final interpretation of fictional texts, and concluded that data mining via visualization can mirror the semantic categorization a fictional text carry. Another study conducted by [43] explored the extent to which concordance is effective in the analysis of fictional discourse. This study demonstrated that concordance can be applied to large data texts in order to generate authentic and credible results that contribute to the interpretation of texts.…”
Section: F Previous Studiesmentioning
confidence: 99%